Social media, saving the food & beverages business in the COVID-19 era? - Rahmawati Rahmawati; Syarifah Hudayah; Ardi Paminto (Cogent Business & Management, 2023)
Covid-19 has caused an economic recession, including uncertainty over the food and beverage sector. One of the layers of business that is vulnerable to pandemic attacks is cafés and restaurants. In early 2020-2022, many café and restaurant businesses have been closed as a series of polemics that have resulted in operational cost losses. At the same time, the government issued regulations related to tightening regional quarantines. Automatically, these rules stimulate a toward in reforming innovation. Based on shifts in consumer behavior since the pandemic, this paper is dedicated to investigating the effects of product delivery innovation (PDI), cashless payments (CP), and social media engagement (SME) on marketing performance (MP). The object of this study is oriented towards 146 cafés and restaurants spread across many major cities in Indonesia. The online survey is centered on café and restaurant management. Systematics and data interpretation via SEM-PLS. The empirical output proves that product delivery innovation and cashless payments have no impact on marketing performance. Uniquely, social media engagement actually has an impact on marketing performance. Besides that, product delivery innovation and cashless payments through social media engagement have an impact on marketing performance. The emergence of COVID-19 in Indonesia shows that social media trends can develop a harmonious relationship between producers and customers. Going forward, the findings of this study have the obsession of promoting a more complex literary lens.
Keywords: 650; cashless payment; social media engagement; food and beverages; marketing performance; product delivery innovation